Pengaruh Gaya Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervening Pada Biro Perekonomian Kantor Gubernur Provinsi Sumatera Barat - Muhammad Zikri Dwitama Rofa; Ramdani Bayu Putra; Dodi Suryadi; Hasmaynelis Fitri (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to investigate the relationship between leadership style, level of work discipline, motivation and employee performance at the Economic Bureau of the Governor's Office of West Sumatra Province, with motivation as an intervening variable. The research method used is a qualitative approach to gain a deeper understanding of organizational dynamics. Data was collected through interviews and observations of employees and leaders at the Economic Bureau. The research results show that effective leadership styles, such as transformative and participative leadership, have a positive influence on employee motivation and performance. On the other hand, a high level of work discipline also has a positive impact on employee motivation and performance through creating a structured and supportive work environment. Employee motivation, as a mediator, plays an important role in linking leadership style, work discipline, and employee performance. This research provides valuable insight into the factors that influence employee performance in the Economic Bureau and their effectiveness on the effectiveness of economic management at the provincial level.